THE ISSUES OF THE SCIENTIFIC SYSTEM OF PSYCHO-LEGAL STUDIES - Nadareishvili, Vakhtang (Georgian Psychological Journal, 2024)
The purpose of the given article is to define the place and importance of psychological science in increasing the effectiveness of theoretical and practical activity directed at normative regulation of social relationships. In particular, the article reviews modern directions of psycho-legal studies, defines the areas of cooperation between psychology and legal studies, identifies the important themes/problem issues, as well as the promising directions in this kind of cooperation. The article also aims to highlight the productivity of a full utilization of the potential of these two areas (psychology and law), as well as of the productivity of multidisciplinary approach, stimulate cooperation between these two areas for the purpose of social security, stability and progress, strengthening legality and law and order, as well as the fight against crime and protection of human rights.